(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Matangaran JR, Anissa IN, Adlan Q, Mujahid M. 2022. Changes in floristic diversity and stand damage of tropical forests caused by logging operations in North Kalimantan, Indonesia. Biodiversitas 23: 6358-6365. Selective cutting of natural forests in Indonesia has been going on for decades. As a consequence, such activities cause disturbances in vegetation cover indicated by changes in diversity and evenness, forest stands damage and mortality of juvenile trees. This research aimed to determine changes in diversity and evenness of vegetation before and after harvesting at seedling, saplings, poles and tree levels, stand damage and forest opening, the number of natural regeneration, and the relationship between felling intensity and forest opening. The research was conducted in a logging concession applying Reduced Impact Logging (RIL) in North Kalimantan by restricting timber cutting to only commercial trees with a diameter of more than 50 cm. The result found 38 tree species in the research plot with average logging intensity of 6.5 trees per hectare. Before and after harvesting, it was found that there were slight changes in diversity and evenness indices at seedling, sapling, pole and tree levels. The percentage of stand damage was 17.8%, and the percentage of forest opening was 19.76 %, which was comparably lower than logging practices in other areas. Nonetheless, we found a strong positive relationship between felling intensity and forest opening. The findings of this study provide another evidence that it is necessary to implement reduced impact logging to reduce damage to forest ecosystems due to selective cutting in the tropical region. It is important to limit the number of trees logged per hectare in order to reduce logging damage and forest opening, minimize impacts on tree species diversity and facilitate natural regeneration.